2020
DOI: 10.1017/jfm.2020.547
|View full text |Cite
|
Sign up to set email alerts
|

Alignment statistics of rods with the Lagrangian stretching direction in a channel flow

Abstract: Abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 55 publications
(118 reference statements)
0
6
0
Order By: Relevance
“…For Re p 1, the models include the Stokes resistance (Brenner 1963(Brenner , 1964Brenner & Cox 1963) and Jeffery torque (Jeffery 1922) for non-spherical particles. In the PP-DNSs without considering the effect of gravity, the weak inertial or inertialess prolate spheroids near the wall tend to align their symmetry axes with the streamwise direction, while the weak inertial or inertialess oblate spheroids preferentially align their symmetry axes with the wall-normal direction (Marchioli et al 2010;Challabotla, Zhao & Andersson 2015b;Zhao et al 2015;Jie et al 2019b;Cui et al 2020bCui et al , 2021. As the particle inertia increases, prolate spheroids have a tendency to tumble, while oblate spheroids preferentially spin in the streamwise-wall-normal plane near the wall (Marchioli et al 2010;Marchioli & Soldati 2013;Challabotla et al 2015a;Zhao et al 2015Zhao et al , 2019.…”
Section: Angular Dynamics Of Spheroidal Particles In Turbulent Channe...mentioning
confidence: 99%
See 1 more Smart Citation
“…For Re p 1, the models include the Stokes resistance (Brenner 1963(Brenner , 1964Brenner & Cox 1963) and Jeffery torque (Jeffery 1922) for non-spherical particles. In the PP-DNSs without considering the effect of gravity, the weak inertial or inertialess prolate spheroids near the wall tend to align their symmetry axes with the streamwise direction, while the weak inertial or inertialess oblate spheroids preferentially align their symmetry axes with the wall-normal direction (Marchioli et al 2010;Challabotla, Zhao & Andersson 2015b;Zhao et al 2015;Jie et al 2019b;Cui et al 2020bCui et al , 2021. As the particle inertia increases, prolate spheroids have a tendency to tumble, while oblate spheroids preferentially spin in the streamwise-wall-normal plane near the wall (Marchioli et al 2010;Marchioli & Soldati 2013;Challabotla et al 2015a;Zhao et al 2015Zhao et al , 2019.…”
Section: Angular Dynamics Of Spheroidal Particles In Turbulent Channe...mentioning
confidence: 99%
“…2019 b ; Cui et al. 2020 b , 2021). As the particle inertia increases, prolate spheroids have a tendency to tumble, while oblate spheroids preferentially spin in the streamwise–wall-normal plane near the wall (Marchioli et al.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical investigations have greatly helped to understand the effect of shape on the dynamics, orientation and alignment of anisotropic particles in turbulence. Many works have been focused on homogeneous and isotropic turbulence (HIT), but important works also investigated the influence of non-homogeneity on the particles dynamics in the presence of more complex flows, such as wall-bounded flows (Marchioli, Fantoni & Soldati 2010;Zhao et al 2015;Zhao & Andersson 2016;Cui et al 2020). Experiments have contributed to a detailed understanding of the dynamics of anisotropic particles, with most of the works in the HIT configuration (Parsa et al 2012;Parsa & Voth 2014;Pujara et al 2018) and only few in turbulent channel flow.…”
Section: Introductionmentioning
confidence: 99%
“…In an Eulerian approach, the alignment with the eigenvectors of the strain rate and the fluid velocity has been studied 18,19,24 . It has been found that a simpler picture emerges if one describes the local alignment in the reference formed in the Lagrangian framework [25][26][27] . The physical image of the Lagrangian reference frame is suggested as below.…”
Section: Introductionmentioning
confidence: 99%